Possible contribution of pannexin‐1 to ATP release in human upper airway epithelia. Issue 2 (10th February 2014) - Ohbuchi, Toyoaki; Takenaga, Fumiko; Hohchi, Nobusuke; Wakasugi, Tetsuro; Ueta, Yoichi; Suzuki, Hideaki
Abstract Pannexins are a family of transmembrane nonselective channel proteins that participate in the release of ATP into extracellular space. Previous studies have suggested that pannexin‐1 (Panx1) may constitute a local autocrine/paracrine system via transmitter ATP in association with the purinergic P2X7 receptor. In this study, we investigate the expressions of Panx1 and P2X7 in human nasal mucosa, together with hypotonic stress‐induced ATP release from this tissue. Twenty men and one woman ranging in age from 10 to 82 years with an average age of 44.2 ± 4.4 years participated in the study. Inferior turbinates were collected from patients with chronic hypertrophic rhinitis during endoscopic endonasal surgery. The expressions of Panx1 and P2X7 were examined by fluorescence immunohistochemistry and quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). We also examined hypotonic stress‐induced ATP release from the turbinate mucosa and the effects of channel blockers in an ex vivo experiment. Substantial expressions of both proteins were observed in human nasal mucosa. The immunoreactivity for Panx1 was stronger than that for P2X7. The presence of the transcripts of Panx1 and P2X7 was also shown by qRT‐PCR. Ten and 100 μmol/L carbenoxolone (a Panx1 channel blocker) significantly inhibited the ATP release from the nasal mucosa, but flufenamic acid (a connexin channel blocker) and gadolinium (a stretch‐activated channel blocker) did not. These results indicate the coexistence of Panx1 and P2X7 in, and Panx1‐dependent ATP release from, the human nasal mucosa, suggesting the possible participation of these molecules in the physiological functions of the upper airway.